ANALISIS KEMAMPUAN BERBICARA SISWA KELAS II MELALUI MODEL PEMBELAJARAN THINK TALK WRITE DI SDN 007 SUNGAI PINANG SAMARINDA - Sri Mulyati (Pendas Mahakam : Jurnal Pendidikan dan Pembelajaran Sekolah Dasar, 2020)
The research aimed at finding out speaking ability of second grade elementary students by using Think Talk Write learning model. The data retrieval was carried out for four days. The problem was lack of teachers’ innovation in improving students’ speaking ability so the researcher decided to carry out this model. The research method was descriptive qualitative. Primary data was taken from this research result and secondary data was taken from published journals. Data analysis techniques were triangulation and data reduction from interview, observations, students’ activities, and students’ presentation results. The result of this study showed that on the first day of observation the students were still in low category, while on the second day to the fourth day, 25 students were in fast category and only 2 students were in medium category. Based on this result, it can be concluded that Think Talk Write learning model can improve speaking ability of second grade elementary students.